Developing a Foundation for Interprofessional Education Within Nursing and Medical Curricula. Issue 5 (September 2016) - Horsley, Trisha Leann; Reed, Trent; Muccino, Keith; Quinones, Donna; Siddall, Viva Jo; McCarthy, Janet
Abstract : Effective teamwork is essential to foster patient safety and promote quality patient care. Students may have limited to no exposure to interprofessional education (IPE) or collaborative practice, therefore making it challenging to learn how to work in teams. This article describes how a nursing and a medical school collaborated to systematically integrate IPE simulations into the curricula so that every graduate from the respective schools received TeamSTEPPS® education and participated in a standardized IPE simulation experience.